EFFECT OF SUPPLEMENTATION OF MANNAN OLIGOSACCHARIDE ON BIOCHEMICAL PRO FILE IN SVVU T17 CROSSBRED PIGS (Indian Journal of Animal Production and Management, 2025)
The present study was conducted to investigate the effect of supplementation of  mannan-oligosaccharide (MOS) on biochemical profile in SVVU T17 crossbred  pigs. Twenty-four SVVU T17 crossbred male grower pigs above 2 months of age  were randomly divided into four groups with six piglets in each group i.e., T0, T1,  T2 and T3 groups. The experiment was conducted for 45 days and at the end of  experiment blood samples were collected for estimation of biochemical profile.  There was a significant decrease (P
Keywords: m a n n a n - o l i g o s a c c h a r i d e; Biochemical profile; SVVU T17 pig